The The Effect of Nitrogen on Methane Gas Flame Propagation Characteristic in Premix Combustion - Djoko Wahyudi; Dani Hari Tunggal Prasetiyo; Alief Muhammad (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
The electric engine is a serious opponent of the fuel engine. However, this does not mean that fossil fuels should be abandoned, but rather makes it a great challenge and a strong reason to develop fossil fuels to be even more efficient. Increasing the combustion efficiency of the current fuel engine can be done in various ways and methods. One of the many ways to increase combustion efficiency in terms of fuel is by mixing the fuel with other compounds. This article examines the effect of mixing variations of methane gas with nitrogen gas. The flame propagation speed in the midpoint of the mixture of stoichiometry (methane-air) and Nitrogen (N2) on the top ignition is 2233.33 mm/s at N2 10% of the third frame and at lower ignition, the speed is 3550.03 mm/s at N2 20% of the second frame. In addition, the bottom ignition experiment has a very large effect on maximizing the speed of flame propagation, especially in the 20% N2 sample. Therefore, the highest improvement in combustion efficiency is obtained by using a 20% N2 mixture and at the bottom ignition condition.